Occupational stress and burnout among midwives: Challenges and consequences for maternal and child health care in Makassar Indonesia - Taureng, Hasnah; Azmi , Intan Suhana Munira Mat; Oo, San San; Aung, Myat Moe Thwe (Science Midwifery, 2024)
Introduction: Stress and burnout are by far more sensitive among the midwifery and nursing professions. Stress can reduce the quality of care and treatment and even pose a risk to countless lives in public center. In addition to causing discomfort that causes problems such as a decrease in talent, if work stress continues. Methodology: A cross-sectional study of 217 midwives, using the Copenhagen Burnout Inventory (CBI) is a comprehensive tool that measures burnout. This study highlights the important role of midwives in improving maternal and child health and the detrimental impact of stress and burnout on healthcare worker. Through the analysis of demographic data and health service statistics, underscore the urgent need for strategic interventions to address health worker burnout and improve the quality and accessibility of health services in Makassar. Conclusion: Implementing effective stress management interventions, healthcare systems can improve job satisfaction, reduce burnout.